Identification and quantification of glutathione and phytochelatins from Chlorella vulgaris by RP-HPLC ESI-MS/MS and oxygen-free extraction - Simmons, Denina B. D; Hayward, Allison R; Hutchinson, Thomas C; Emery, R. J. Neil (Analytical and bioanalytical chemistry, 2009)
Phytochelatins are short, cysteine-containing, detoxification peptides produced by plants, algae, and fungi in response to heavy metal exposure. These peptides auto-oxidize easily. Current extraction protocols do not adequately address losses of phytochelatins because of their oxidation and the use of indirect methods for quantification. Method enhancements include the use of an argon environment during extraction to reduce auto-oxidation, the use of glycine-¹³C2-labeled glutathione as an internal standard, and an electrospray ionization source with a triple quadrupole mass spectrometer as a detector. The method-detection limits were 0.081 μM for glutathione, 0.440 μM for phytochelatin 2, and 0.120 μM for phytochelatin 3. These detection limits were comparable to similar studies and were not compromised incorporating these adjustments. The use of a labeled internal standard and an inert gaseous environment during sample preparation greatly improved calibration linearity and sensitivity. Furthermore, phytochelatin degradation was significantly reduced and more accurately tracked. Previous studies involving phytochelatin analyses have likely been subject to higher variability caused by this propensity for phytochelatins to degrade rapidly in air. The method adjustments were simple and cost-effective and allowed phytochelatin analyses to be performed for hours at a time with minimal auto-oxidation. [graphic removed]